Evaluation of Established Methods for DNA Extraction and Primer Pairs Targeting 16S rRNA Gene for Bacterial Microbiota Profiling of Olive Xylem Sap - Haro, Carmen; Anguita-Maeso, Manuel; Metsis, Madis; Navas-Cortés, Juan A.; Landa, Blanca B. (Frontiers in Plant Science, 2021)
Next Generation Sequencing has revolutionized our ability to investigate the microbiota composition of diverse and complex environments. However, a number of factors can affect the accuracy of microbial community assessment, such as the DNA extraction method, the hypervariable region of 16S rRNA gene targeted or the PCR primers used for amplification. The aim of this study was to assess the influence of commercially available DNA extraction kits and different primer pairs to provide a nonbiased vision of the composition of bacterial communities present in olive xylem sap. For that purpose, branches from ‘Picual’ and ‘Arbequina’ olive cultivars were used for xylem sap extraction using a Scholander chamber device. The DNA extraction protocol significantly affected xylem sap bacterial community assessment. That, resulted in significant differences in alpha (Richness) and beta diversity (UNIFRAC distances) metrics among DNA extraction protocols, with the 12 DNA extraction kits evaluated being clustered in four groups behaving differently. Although the core number of taxa detected by all DNA extraction kits included four phyla, seven classes, 12 orders, and 16 or 21 families, and 12 or 14 genera when using the Greengenes or Silva database for taxonomic assignment, respectively, some taxa, particularly those identified at low frequency, were detected by some DNA extraction kits only. The most accurate depiction of a bacterial mock community artificially inoculated on sap samples was generated when using the PowerPlant DNA extraction Kit, the combination of 799F/1193R primers amplifying the hypervariable V5-V7 region and the Silva 132 database for taxonomic assignment. The DESeq2 analysis displayed significant differences among genera abundance between the different PCR primer pairs tested. Thus, Enterobacter, Granulicatella, Prevotella and Brevibacterium presented a significant higher abundance in all PCR protocols when compared with primer pair 799F/1193R, while the opposite was true for Pseudomonas and Pectobacterium. The methodological approach followed in this study can be useful to optimize plant-associated microbiome analysis, especially when exploring new plant niches. Some of the DNA extraction kits and PCR primers selected in this study will contribute to better characterize bacterial communities inhabiting within the xylem sap of olives or other woody crop species.